A new Dead Sea pollen record reveals the last glacial paleoenvironment of the southern Levant. (15th June 2019) - Miebach, Andrea; Stolzenberger, Sophie; Wacker, Lisa; Hense, Andreas; Litt, Thomas
Abstract: The southern Levant is a key region for studying vegetation developments in relation to climate dynamics and hominin migration processes in the past due to the sensitivity of the vegetation to climate variations and the long history of different anthropogenic occupation phases. However, paleoenvironmental conditions in the southern Levant during the Late Pleistocene were still insufficiently understood. Therefore, we investigated the vegetation and fire history of the Dead Sea region during the last glacial period. We present a new palynological study conducted on sediments of Lake Lisan, the last glacial precursor of the Dead Sea. The sediments were recovered from the center of the modern Dead Sea within an ICDP campaign. The palynological results suggest that Irano-Turanian steppe and Saharo-Arabian desert vegetation prevailed in the Dead Sea region during the investigated period (ca. 88, 000–14, 000 years BP). Nevertheless, Mediterranean woodland elements significantly contributed to the vegetation composition, suggesting moderate amounts of available water for plants. The early last glacial was characterized by dynamic climate conditions with pronounced dry phases and high but unstable fire activity. Anatomically modern humans entered the southern Levant during a climatically stable phase (late MIS 4–MIS 3) with diverse habitats, constant moisture availability, and low fire activity. MIS 2 was the coldest phase of the investigated timeframe, causing changes in woodland composition and a widespread occurrence of steppe. We used a biome modeling approach to assess regional vegetation patterns under changing climate conditions and to evaluate different climate scenarios for the last glacial Levant. The study provides new insights into the environmental responses of the Dead Sea region to climate variations through time. It contributes towards our understanding of the paleoenvironmental conditions in the southern Levant, which functioned as an important corridor for human migration processes. Highlights: New pollen and micro-charcoal record from Lake Lisan (the last glacial precursor of the Dead Sea). The results reveal a mosaic of Irano-Turanian steppe, Saharo-Arabian desert, and woodland elements. Anatomically modern humans lived in a stable, diverse environment with low fire activity. Different climate scenarios are evaluated using biome modeling.